Artkosmos-Fragmente. Stefan Holitschke. 2011 - Meidl, E (2013)
Stefan Holitschke's slim volume adds to the vast amount of Arctic and Antarctic lyric responses to the extreme environments of the polar regions. Published by Asaro Verlag 2011 , its cover shows an ice carving of a polar bear whose head seems to have suffered from melting. Arktokosmos is a curious edition which does not give any inforn:iation about the author: one must google his biographical details to find out that his 'lyrical fragments' were written as a result of wintering on Spitsbergen. According to his own web site he is a 'dedicated IT specialist with additional skills in circumpolar studies, law, economy and energy business'. Arktokosmos seems to be Holitschke's first foray into poetry.